IMPROVING LISTENING COMPREHENSION OF GRADE X STUDENTS OF SMAK GPID SUMBERSARI THROUGH SHORT STORIES - Handayani, Ni Luh Sri (BAHASANTODEA, 2015)
Abstract This classroom action research was conducted to improve listening comprehension of grade X students of SMAK GPID Sumbersari through short stories. The subjects of action were 17 students of class X IPA of SMAK GPID Sumbersari. This research had two cycles. There were four meetings in cycle 1 and two meetings in cycle 2. The material was narrative text. The qualitative data were taken from the observation sheets, field notes, and questionnaire and the quantitative data were taken from test 1 and test 2. The researcher found that most of the students were still confused when they listened to the short stories from the recorder since they were accustomed to listening to short stories dictation by their own teacher not listening directly from the recorder, but then they more concerned and looked more enthusiastic so they could understand the short stories that they heard from the recorder. Observation sheet and questionnaire results indicate that they were happy to interact with their friends in group. The researcher found that in cycle 1, there were 11 or 64.71 percent students who were successful with the test and 6 students or 35.29 percent students who were not successful yet. After reflecting the researcher revised the plan based on three aspects: preparation, time management, and action. In cycle 2, there were 15 or 88.24 percent students who were successful and 2 students or 11.76 percent were not successful. Both the percentages indicate that there were enhancements of the students who succeed in cycle 1 of reaching KKM (70) eventually increased in cycle 2. Thus, it is concluded that this technique is effective to be applied to students’ listening comprehension. Keywords: Improving, Listening Comprehension and Short Stories